Ectoparasitic insects (Diptera: Streblidae and Siphonaptera: Ischnopsyllidae) of bats from Iquitos and surrounding areas (Loreto, Peru) - Autino, Analia Gladys (2011)
Based on specimens collected from bats of different families, we add new species and extend the known ecological distribution and host associations of insect ectoparasites of bats in Peru. New information is provided for the distribution of 26 species of parasites (25 Diptera and 1 Siphonaptera: Ischnopsyllidae). Four species (Neotrichobius ectophyllae, Strebla galindoi, Strebla paramirabilis and Myodopsylla wolffsohni wolffsohni) are new for Peru and 16 represent new records for the department of Loreto. Also, we found 17 new host-ectoparasite relationships. Of note, we found remarkable new association between Neotrichobius delicatus and bat species from the families Molossidae and Noctilionidae and a novel association between Paradyschiria parvula and a species of Vespertilionidae. Host-ectoparasite specificity was recorded with 14 species as monoxenous, three oligoxenous, seven pleioxenous and two polyxenous.